2020
DOI: 10.1007/s00432-020-03327-2
|View full text |Cite|
|
Sign up to set email alerts
|

Results of a randomized trial of treatment modalities in patients with low or early-intermediate risk prostate cancer (PREFERE trial)

Abstract: Purpose The optimal treatment for patients with low to early-intermediate risk prostate cancer (PCa) remains to be defined. The randomized PREFERE trial (DRKS00004405) aimed to assess noninferiority of active surveillance (AS), external-beam radiotherapy (EBRT), or brachytherapy by permanent seed implantation (PSI) vs. radical prostatectomy (RP) for these patients. Methods PREFERE was planned to enroll 7600 patients. The primary endpoint was disease specific survival. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The importance of conducting feasibility trials has been shown multiple times, with warning examples such as the PREFERE prostatic cancer trial. 56 The RCT was designed to show non-inferiority of active surveillance, external-beam radiotherapy and brachytherapy by permanent seed implantation to radical prostatectomy with a planned sample size of 7600 patients. However, the trial was stopped early due to poor accrual as only 459 patients agreed to participate within a time period between 2012 and 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of conducting feasibility trials has been shown multiple times, with warning examples such as the PREFERE prostatic cancer trial. 56 The RCT was designed to show non-inferiority of active surveillance, external-beam radiotherapy and brachytherapy by permanent seed implantation to radical prostatectomy with a planned sample size of 7600 patients. However, the trial was stopped early due to poor accrual as only 459 patients agreed to participate within a time period between 2012 and 2016.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been no randomized controlled trials comparing modern-day active surveillance inclusive of protocol-driven repeat prostate biopsies to upfront treatment of prostate cancer other than the recent PREFERE study [6] published in 2021; however, this study suffered from poor accrual and the trial was terminated prematurely. There are three randomized trials comparing active monitoring or watchful waiting to treatment, which has given some insight into which patients may be offered active surveillance.…”
Section: Randomized Trialsmentioning
confidence: 99%
“…Much of the available clinical data remains inconclusive due to the lack of concrete control groups and the possibility of confounding variables [ 29 , 30 ]. There were also some attempts to assess the effectiveness of the different treatment modalities, but such studies were prematurely closed due to decreases in longitudinal active surveillance and thus potential resulting toxicity-related concerns [ 31 ]. Hence, randomized data directly comparing the efficacies and outcomes of survival for various RT techniques are currently lacking on a national scale [ 20 ].…”
Section: Introductionmentioning
confidence: 99%